A population of Pax7-expressing muscle progenitor cells show differential responses to muscle injury dependent on developmental stage and injury extent - Knappe, Stefanie; Zammit, Peter; Knight, Robert (Frontiers in Aging Neuroscience, 2015)
Muscle regeneration in vertebrates occurs by the activation of quiescent progenitor cells that express pax7 and replace and repair damaged fibers. We have developed a mechanical injury paradigm in zebrafish to determine whether developmental stage and injury size affect the regeneration dynamics of damaged muscle. We found that both small, focal injuries and large injuries affecting the entire myotome lead to the expression of myf5 and myogenin. Their expression was prolonged in older larvae, indicating a slower process of regeneration. We characterized the endogenous behavior of a population of muscle-resident Pax7-expressing cells using a pax7a:eGFP transgenic line and found that GFP+ cell migration in the myotome dramatically declined between 5 and 7 days post fertilization (dpf). Following a small injury, we observed that GFP+ cells responded by extending processes, before migrating to the injured fibers. Furthermore, these cells responded more rapidly to injury in 4dpf larvae compared to 7dpf. Interestingly, we did not see GFP+ fibers after repair of small injuries, indicating that pax7a-expressing cells did not contribute to fiber formation in this injury context. On the contrary, numerous GFP+ fibers could be observed after a large single myotome injury. Both injury models were accompanied by an increased number of proliferating GFP+ cells, which was more pronounced in larvae injured at 4dpf than 7dpf, This indicates intriguing developmental differences, even at these relatively early ages. Our data also suggests an interesting disparity in the role that pax7a-expressing muscle progenitor cells play during muscle regeneration, which may reflect the extent of muscle damage.